Origin of anomalous inverse notch effect in bulk metallic glasses. (November 2015) - Pan, J.; Zhou, H.F.; Wang, Z.T.; Li, Y.; Gao, H.J.
Abstract: Understanding notch-related failure is crucial for the design of reliable engineering structures. However, substantial controversies exist in the literature on the notch effect in bulk metallic glasses (BMGs), and the underlying physical mechanism responsible for the apparent confusion is still poorly understood. Here we investigate the physical origin of an inverse notch effect in a Zr-based metallic glass, where the tensile strength of the material is dramatically enhanced, rather than decreased (as expected from the stress concentration point of view), by introduction of a notch. Our experiments and molecular dynamics simulations show that the seemingly anomalous inverse notch effect is in fact caused by a transition in failure mechanism from shear banding at the notch tip to cavitation and void coalescence. Based on our theoretical analysis, the transition occurs as the stress triaxiality in the notched sample exceeds a material-dependent threshold value. Our results fill the gap in the current understanding of BMG strength and failure mechanism by resolving the conflicts on notch effects and may inspire re-interpretation of previous reports on BMG fracture toughness where pre-existing notches were routinely adopted.